2013
DOI: 10.1002/em.21759
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic bioactivation of constituents of a diesel exhaust particle extract by the human lung

Abstract: The ability of the human lung to catalyze genotoxic bioactivation of constituents of diesel exhaust particle (DEP) extract (DEPE) and the identity of the lung enzymes involved in the bioactivation were investigated using human lung tissues obtained from surgical resections. Genotoxicity was determined by lung S9-catalyzed mutagenicity of DEPE constituents to Salmonella typhimurium TA98NR in the Ames test and by DEPE-induced pneumocyte DNA damage response as determined by γH2Ax expression in ex vivo tissues. S9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 100 publications
(205 reference statements)
0
7
0
Order By: Relevance
“…However, to specifically reveal the potential carcinogenic effects of PAHs, application of organic extracts is more relevant. Although the genotoxicity of DEP extracts may be easily tested by standardized, well-established tests including cytotoxicity measurement [20], Ames test [20,21], analysis of double strand DNA breaks [21], apoptosis, frequency of micronuclei [22], bulky DNA adducts formation or oxidative DNA damage [12], for a comprehensive assessment of the biological processes induced by the DEP extracts the treatment of the whole genome gene expression analysis is a valuable tool.…”
Section: Introductionmentioning
confidence: 99%
“…However, to specifically reveal the potential carcinogenic effects of PAHs, application of organic extracts is more relevant. Although the genotoxicity of DEP extracts may be easily tested by standardized, well-established tests including cytotoxicity measurement [20], Ames test [20,21], analysis of double strand DNA breaks [21], apoptosis, frequency of micronuclei [22], bulky DNA adducts formation or oxidative DNA damage [12], for a comprehensive assessment of the biological processes induced by the DEP extracts the treatment of the whole genome gene expression analysis is a valuable tool.…”
Section: Introductionmentioning
confidence: 99%
“…Polycyclic aromatic hydrocarbons (PAHs) and nitrorarenes (nitro-PAHs) are some of the primary chemical classes in DEP that are associated with the carcinogenicity and mutagenicity of DEP [US EPA, 2002]. Mechanistic support for this has been shown recently by the demonstration that the human lung is able to bio-activate the organics in DEP to produce detectable mutagenic activity via CYP1A1 and NQO1 enzymes and that this activation is associated with the mutagenicity of PAHs and nitro-PAHs [Iba and Caccavale, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…Comet assay demonstrating increased DNA damage in IM9 or A549 cells exposed to MC prior to DEP has shown that CYP1A1 is involved in the increased generation of ROS resulting in increased DNA damage in these cells. In vivo and in vitro studies have also shown that bioactivation of PAHs present in DEPs by CYP1A isoenzymes is partially responsible in mediating genotoxic response as seen through DNA strand breaks or through formation of DNA adduct (8-OHdG) formation in exposed cells 8,48,[51][52][53] . The reduction in the extent of DNA damage following preincubation of A549 or IM9 cells with α-NF, has further demonstrated the role of PAH metabolising CYP1A1 in the metabolic activation and toxicity of DEP.…”
Section: Discussionmentioning
confidence: 99%